THE PHENOMENON OF EARLY MARRIAGE IN INDONESIA ISLAMIC FAMILY LAW PERSPECTIVE - Suci Br Sitepu (Academic Solution Publisher, 2025)
Early marriage is a phenomenon that continues to be of concern in Indonesia, especially in areas with strong cultural traditions. This study aims to examine the phenomenon of early marriage from the perspective of Islamic family law, highlighting the factors that drive the practice and its impact on individuals and society. Using a normative juridical approach, the study finds that although Islamic law provides for a marriage age limit based on physical and mental capability, the practice of early marriage is often driven by social pressure, poverty and lack of education. The article recommends the need for synergy between Islamic law and national regulations to protect children's rights and realize the goal of harmonious marriage in accordance with maqashid sharia.